The Advancement Stage of Gastric Cancer and the Levels of CEA and Ca19-9 in Serum and Peritoneal Lavage - Michał Bąk; Magdalena Wojciech; Adrianna Pielech; Sylwia Holka; Marek Zawadzki; Dawid Murawa (Biomedicines)
Background: This study aimed to analyze the relationship between the levels of tumor markers—specifically, carcinoembryonic antigen (CEA) and Ca19-9 antigen—determined in both serum (sCEA and sCa19-9) and intraoperative peritoneal washings (pCEA and pCa19-9) and the advanced stage of gastric cancer (including the occurrence of cancer cells in cytology from abdominal fluid). Methods: This study included 47 patients with histopathologically confirmed gastric cancer or gastroesophageal junction cancer who underwent surgical treatment. The material for the cytological examination and assessment of CEA and Ca19-9 concentrations in peritoneal fluid was collected intraoperatively. Later, blood was drawn to assess the CEA and Ca19-9 concentrations in blood serum. Results: There was a statistical correlation between a positive cytology result or the presence of peritoneal carcinomatosis and a positive result for the tumor markers obtained from abdominal washings. This correlation was not observed with marker levels obtained from blood serum. The pCEA marker was highly sensitive (93.3%) and specific (93.8%) for detecting cancer cells. The pCa19-9 marker was less effective in detecting cancer but matched pCEA in identifying the absence of cancer. No differences were observed in sCEA and sCA19-9 levels between patients who underwent neoadjuvant chemotherapy and those who did not receive this treatment. However, statistical analysis showed that this relationship did not apply to pCEA and pCa19-9 levels. Conclusions: Intraoperative determinations of tumor marker levels in peritoneal washings may be a predictive factor for a poor prognosis in patients with gastric cancer.